Immunomodulatory effect of Ganoderma lucidum polysaccharide extract on peritoneal macrophage function of BALB/c mice: GL-PS extract on peritoneal macrophage function - Hu, Yanling; Lin, Zhongxiang; Fu, Hairong; Xia, Jing; Xiong, Wei; Li, Guoli (Cellular and Molecular Biology, 2022)
Ganoderma lucidum has been suggested as a natural immunomodulator. It is not yet clear exactly which combination of this extract is responsible for its immunomodulatory effects. Still, it appears that the 3-complement (CR3) receptor on the surface of immune cells acts as a receptor for beta-glucans (glucan-8), which is the main component of this extract. Since glucose-6-phosphate dehydrogenase (G6PD) plays a vital role in regulating macrophage functions, including nitric oxide production, we considered the effect of this extract on viability, G6PD enzyme activity, and nitric oxide (NO) production in peritoneal BALB/c macrophages. First, peritoneal macrophages of BALB/c mice were isolated and treated with concentrations (0.001, 0.01, 0.1, 1, 10, and 100 g/ml) of Ganoderma lucidum polysaccharide extract (GL-PS). After 24 hours of incubation by MTT test, we evaluated the viability of macrophages, and the effective dose was determined to be 0.1g/ml. To determine the specific activity of glucose-6-phosphates, they were incubated with GI-PS for 24 hours at a 0.1 mg/ml dose. Determination of protein concentration was obtained by the Bradford method in cell supernatant extract. Also, after 18 hours of incubation, the amount of nitric oxide (NO) production was measured using Grace colorimetric method. According to the results, a dose of 0.1μg/ml of Ganoderma lucidum polysaccharide extract had the most significant effect on the viability (stimulation coefficient) of peritoneal macrophages compared to other amounts (p <0.05). It was also found that a dose of 0.1μg/ml GL-PS increases NO production and the specific activity of the G6PD enzyme (p <0.05). Ganoderma lucidum, a medicinal fungus, is widely used in East Asian countries, especially in China, to increase the quality of life and longevity. After this study, we concluded that GL-PS extract has an immunomodulatory effect on macrophage activity. Therefore, the polysaccharide extract of this fungus can be used as a strengthening agent of the phagocytic system against infectious agents and pathogens such as the Leishmania parasite because of the production of nitric oxide by macrophages plays an essential role in defense against them.